COMPARATIVE EVALUATION OF IMMEDIATE AND LONG-TERM RESULTS OF HERNIATION BY THE METHOD OF «ONSTEP» AND I.L. LICHTENSTEIN IN ADULTS - Владимир Викторович Шейерман; Андрей Игоревич Баранов; Юрий Викторович Валуйских; Анастасия Вадимовна Смирнова (Медицина в Кузбассе)
Aim – of the study was a comparative assessment of the immediate and long-term results of herniation by I.L. Lichtenstein and ONSTEP in adult patients with inguinal hernias.